2020
DOI: 10.12806/v19/i2/a1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Global Mindset and Intercultural Competence Through the Framework of Emotionally Intelligent Leadership

Abstract: Alongside the growing emphasis on global education within higher education is a greater focus on global leadership and global citizenship within leadership education. In this application manuscript the authors provide examples and discussion of how they have used the Emotionally Intelligent Leadership model as a framework for teaching leadership courses focused on intercultural competence and global mindset. Two specific courses are highlighted, and the authors provide their reflections and implications for le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The key facets of consciousness of self, others, and context-and many of the accompanying capacities (e.g., emotional self-awareness, authenticity, displaying empathy, capitalizing on difference, developing relationships, managing conflict, analyzing the group, assessing the environment)-are foundational for work around equity, inclusion, and social justice. The facets and capacities, in conjunction with models that center diversity, equity, inclusion, and social justice, can help leadership learners develop the knowledge, capacities, and commitment to make contexts more inclusive and equi-table (Haber-Curran, 2017). As an example, the University of Minnesota's Multicultural Student Engagement offers a day-long workshop focused on EIL for student leaders of cultural organizations; the workshop focuses on specific EIL capacities identified by the center's staff as critical for leading culturally-based student organizations, and students earn a certification for completing the workshop.…”
Section: Critiques and Considerationsmentioning
confidence: 99%
“…The key facets of consciousness of self, others, and context-and many of the accompanying capacities (e.g., emotional self-awareness, authenticity, displaying empathy, capitalizing on difference, developing relationships, managing conflict, analyzing the group, assessing the environment)-are foundational for work around equity, inclusion, and social justice. The facets and capacities, in conjunction with models that center diversity, equity, inclusion, and social justice, can help leadership learners develop the knowledge, capacities, and commitment to make contexts more inclusive and equi-table (Haber-Curran, 2017). As an example, the University of Minnesota's Multicultural Student Engagement offers a day-long workshop focused on EIL for student leaders of cultural organizations; the workshop focuses on specific EIL capacities identified by the center's staff as critical for leading culturally-based student organizations, and students earn a certification for completing the workshop.…”
Section: Critiques and Considerationsmentioning
confidence: 99%
“…In the "cooperative learning intervention on physical education students' task and selfapproach goals, and emotional intelligence; the same physical education teacher, an expert in cooperative learning, conducted all sessions. Results showed that the cooperative learning framework helped increase students' self-approach goals and their emotional control and regulation, and empathy" (Rivera-Pérez et al, 2021;Manca et al, 2021;Arifin et al, 2020;Haber-Curran & GuramatunhuCooper, 2019). "The urgency and interest to produce graduates who are ready for the global marketplace have never been more prevalent amongst educators.…”
Section: Promoting and Reinforcing International Cooperationmentioning
confidence: 99%